FRI0494 Arthritis Post Chikungunya Fever: Clinical Profile of A Population of Patients in A Secondary Care Hospital. (15th July 2016) - Losanto, J.; Ojeda, A.; Giménez, F.
Abstract : Background: Chikungunya fever is a viral disease caused by an alphavirus that belongs to the Togaviridae family, it is transmitted by mosquitoes of the gender Aedes. Acute symthomps manifests with high fever, skin rash and arthritis. A high percentage of patients can develop severe and disabling poliarthritis. In 2015 there was an outbreak of this desease in outskirts of the capital city, presenting several cases of arthritis of chikungunya fever Methods: Retrospective, descriptive and cross-sectional study of patients who consulted in a secondary care hospital from Villa Elisa city, for persistent joint pain after chikungunya's fever in the period from March to June of 2015. It was conducted describing the characteristics of clinical state, demographic, treatment and patient outcomes. Statistical analysis was performed with SPSS19.0 program. The qualitative variables were expressed as frequencies and percentages, quantitative variables in mean. Results: 26 patients from the capital city and outskirts were included, 92% of females with the average age of 47.2 years old. The average duration of acute fever was 2.86 days. The predominant symptoms were headache (76.9%), joint pain (92.3%). 92.3% had skin rash in the acute stage, with an average duration of 4.5 days. The joint symptoms began after an average of 14 days after the fever started. The metacarpal phalangeal and interphalangeal joints were affected in 73% of patients, the radiocarpal joints and knees in 76.9%, shoulders in the 50% and feet in 92.3%. All patients were treated with NSAIDs and 20/26 patients (76.9%) was added prednisone at a dose of 40 mg/day with fast and gradual tapering treatment in two weeks, with 92.3% with partial or total relief of symptoms. In 2 patients (7.6%) was decided to add methotrexate for recurrence of the arthritis, whit the decrease of corticosteroids doses. Conclusions: Chikungunya's fever is a major public health problem with increasing cases reports in urban areas, especially for its ability to generate medium and long-term rheumatological complications. It is important to mention the high frequency of hand and feet involvement, leading to several degrees of disability as well impairments, even laboral absenteeism because of the intensity of the pain. Even though the follow-up period is short, it is highlighted the excellent response to this treatment with short time of corticosteroids, although it is needed a longer follow up to define the appropriate treatment according to the evolution and outcome of cases, and with this develop protocols for such cases. Disclosure of Interest: None declared